Process improvement and CMMI® for systems and software - Kenet, Ron S.; Baker, Emanuel R. , 1934- (CRC Press, 2010)
Offers an approach for achieving cost-effective process improvements for systems and software. Focusing on planning, implementation and management in system and software processes, this book presents an overview of basic strategic planning models and covers the concepts and approaches for system and software measurement, testing, and improvements